Medikamentös induzierte Schlafendoskopie - quo vadis?: Bestandsaufnahme und Ausblick - Herzog, Michael; Maurer, Joachim T. (HNO, 2017)
Background: Drug-induced sedation endoscopy (DISE) is a diagnostic procedure which allows evaluation of the collapsibility of the upper airway. According to expert opinion, it is possible to imitate nocturnal collapsibility and perform a realistic investigation of the site of obstruction and vibration. This should enable sufficient and precise therapeutic advice to be given solely on the basis of clinical assessment. Objective: The current publication critically evaluates the present state of development of DISE and its potential indications. Materials and methods: A PubMed literature research was performed using “sleep” and “endoscopy” or “DISE” as keywords. Relevant publications were evaluated. Results: The present publication provides a historical summary of the available publications and relates these to other methods for examining obstructive sleep apnea. The present state of DISE in terms of drugs applied, grading systems, and validity is evaluated. Indications for DISE are described and critically discussed on the basis of literature data. Conclusion: DISE provides deep insights into the genesis of obstructions of the upper airway and snoring. Although its value for diagnosis and treatment of sleep-disordered breathing could not yet be demonstrated for all non-CPAP (continuous positive airway pressure) therapies, DISE could identify predictive parameters some methods. Further potential indications for DISE might be predictive examinations for mandibular advancement devices and respiration-synchronous neurostimulation of the hypoglossal nerve. DISE will thus remain a valuable diagnostic tool for obstructive sleep apnea and rhonchopathy.